Zastosowanie liniowej analizy dyskryminacyjnej w badaniu cech różnicujących klientów wybranych banków komercyjnych - Jefmański, Bartłomiej (The Application of Linear Discriminant Analysis in Research on Features Differentiating Clients of Selected Commercial Banks, 2006)
A lot of studies on a discriminative analysis point to its two main goals: predictive and descriptive. The present article is a characteristic of descriptive aspects of the discriminative analysis. The formulae and results of the calculations essential for the analysis are presented using an empirical example of marketing research carried out among clients of three banks: Kredyt Bank, Lukas Bank and BGŻ.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 288-299